2022
DOI: 10.1002/adma.202208378
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Perturbed Multiresonance TADF Emitter Enables High‐Efficiency and Ultralow Efficiency Roll‐Off Nonsensitized OLEDs with Pure Green Gamut

Abstract: Multiresonance (MR)‐induced thermally activated delayed fluorescence (TADF) emitters based on B‐ and N‐embedded polycyclic aromatics are desirable for ultrahigh‐definition organic light‐emitting diodes (OLEDs) due to their high photoluminescence quantum yield (PLQY) and narrow bandwidth. But the reverse intersystem crossing (RISC) rates of MR‐TADF emitters are usually small, resulting in severe device efficiency roll‐off at high brightness. To solve this issue, a sensitizer for the MR‐TADF emitter has been req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 68 publications
0
38
0
Order By: Relevance
“…On the other hand, for catering to the various molecular systems, new controlling mechanisms of triplet properties should be further explored. Similar to halogenation, incorporating electronwithdrawing phosphine oxide groups 48 or metal perturbation 49 into TADF emitters is a possibly feasible pathway. Utilizing the characteristics of triplet valleys of spirofluorene or spirofluorene xanthene instead of fluorene as the confined skeleton is also a promising strategy for regulating the triplet nature.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%
“…On the other hand, for catering to the various molecular systems, new controlling mechanisms of triplet properties should be further explored. Similar to halogenation, incorporating electronwithdrawing phosphine oxide groups 48 or metal perturbation 49 into TADF emitters is a possibly feasible pathway. Utilizing the characteristics of triplet valleys of spirofluorene or spirofluorene xanthene instead of fluorene as the confined skeleton is also a promising strategy for regulating the triplet nature.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%
“…The EQE max of the 177 device was 35.8% and EQE remained at 32.3% at 10 000 cd m −2 . 101 Heavy-atom integration into the TADF molecule could significantly promote the RISC process. Subsequently, they further reported a pure green multi-resonance TADF molecule 178 and 179 by introducing a peripheral heavy atom selenium onto the parent BN-Cz molecule.…”
Section: Highly Efficient Tadf Emitters Based On Three-coordinate Org...mentioning
confidence: 99%
“…Yang et al also reported green MR-TADF emitters through coordination of Au with B, N-doped PAH cores, which exhibit high RISC rate constants (2.3 × 10 7 s −1 ) and small device efficiency roll-off at high luminance. 37 However, it should be noted that the majority of present MR-TADF-based OLEDs were fabricated by vacuum deposition, while the development of solution-processed MR-TADF emitters suitable for the fabrication of low-cost and large-area OLEDs has lagged behind and is still to be addressed. 38–43…”
Section: Introductionmentioning
confidence: 99%